A152: Safety and Effectiveness of Adalimumab in Children With Polyarticular Juvenile Idiopathic Arthritis Aged 2 to 4 Years. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Kingsbury, Daniel J.; Quartier, Pierre; Karunaratne, Piyalal M.; Kalabic, Jasmina; Kupper, Hartmut
Abstract : Background/Purpose: Adalimumab (ADA) is approved for use in moderate to severe juvenile idiopathic arthritis (JIA) in patients (pts) ≥4 years (yrs) old in the US, EU, and Japan, and was recently approved in EU for pts aged 2 to <4 yrs old. However, limited data are available in pts <4 yrs old. The objective of this study was to assess the safety and effectiveness of ≥1 year of ADA therapy in pts aged 2 to <4 yrs old or ≥4 yrs old weighing <15 kg with moderately to severely active polyarticular JIA. Methods: This was an international, multicenter, open‐label, phase 3b study where JIA pts were treated with ADA 24 mg/m 2 (maximum=20 mg/dose) every other week (wk) +/− methotrexate for up to 120 weeks (wks) until achieving the limit for age (≥4 yrs) and weight (≥15 kg). Adverse events (AEs) were summarized for all completed visits. As clinical effectiveness endpoints, American College of Rheumatology pediatric (PedACR) 30/50/70/90 responses and JIA outcome parameters (PhGA, PaGA, DICHAQ, AJC73, LOM69, CRP, TJC, SJC, and POM75) were collected at each study visit. Results: 32 pts were enrolled in this study, and 31 (97%) completed 24 weeks (wks) of treatment. The mean age at baseline was 3 yrs, with a mean JIA disease duration of 12 months. Baseline disease activity was consistent with moderately to severely active JIA, with a mean AJC of 10.0. Through 120 wks, 2 pts withdrew due to AEs (JIA worsening or flare) and 4 withdrew for other reasons. 26 (81%) pts completed the study after achieving age and weight termination criteria, with 13 pts completing wk 96 and 3 pts completing wk 120. A total of 29 (91%) reported at least 1 AE. AE incidence rates included: any AEs (91%), serious AEs (16%), infectious AEs (78%), and serious infections (9%). No deaths, malignancies, or opportunistic infections were reported. 90% and 92% of pts had achieved PedACR30 at wk 24 and 96, respectively. High PedACR 50/70/90 response rates were achieved at wk 24 (83, 73, and 37%, respectively) and maintained through wk 96 (92, 77, and 62%, respectively). Statistically significant improvements in other JIA outcomes were also observed (Table1 ). Growth, as measured by height and weight, was not adversely affected by ADA treatment. Mean change (SD) from baseline to week 60 was +9.5 cm (2.34) for height and +2.66 kg (0.98) for weight and at week 96 was +15.2 cm (3.48) for height and +4.38 kg (1.44) for weight. AJC, active joint count; CRP, C‐reactive protein; DI‐CHAQ, Disability Index Childhood Health Assessment Questionnaire; LOM, limitation of motion; PaGA, Parent's Global Assessment; PhGA, Physician's Global Assessment; POM, pain on motion; SJC, swollen joint count; TJC, tender joint count; VAS, visual analog scale of 0–100 mm. Conclusion: In this very young population with polyarticular JIA, primary clinical trial data revealed that the safety profile and effectiveness of ADA were comparable to that observed in older children with JIA. No adverse effects on growth were observed.